The millennium development goals : strategic implications for the Latin American and Caribbean statistical systems - Cervera-Ferri, José Luis (CEPAL SantiagoCL, 2007)
Presents a synthesis on the main technical and institutional challenges and opportunities facing the statistical institutes in Latin America and the Caribbean, with regard to the monitoring of the MDGs.